2016
DOI: 10.1080/00031305.2015.1077728
|View full text |Cite
|
Sign up to set email alerts
|

Variations of QQ Plots: The Power of Our Eyes!

Abstract: In statistical modeling we strive to specify models that resemble data collected in studies or observed from processes. Consequently, distributional specification and parameter estimation are central to parametric models. Graphical procedures, such as the quantile-quantile (Q-Q) plot, are arguably the most widely used method of distributional assessment, though critics find their interpretation to be overly subjective. Formal goodness-of-fit tests are available and are quite powerful, but only indicate whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 28 publications
1
49
0
Order By: Relevance
“…Packages("forecast") library(forecast) library(readxl) worldcovid19 <-read_excel("Italycovid19.xlsx") View(worldcovid19) tsworldcovid19 <-ts (Italycovid19$'daily registered Cases', frequency Z 1,start Z c(15/02/2020,1)) tsworldcovid19 <-ts (Italycovid19$'daily recovered Cases', frequency Z 1,start Z c(15/02/2020,1)) plot(tsworldcovid19) A data driven predictive model approach for COVID-19 3 The 60-days COVID-19 forecasting graphs of register along recovery cases (Fig. 4), and normalized QQ plots 9 were computed ( Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…Packages("forecast") library(forecast) library(readxl) worldcovid19 <-read_excel("Italycovid19.xlsx") View(worldcovid19) tsworldcovid19 <-ts (Italycovid19$'daily registered Cases', frequency Z 1,start Z c(15/02/2020,1)) tsworldcovid19 <-ts (Italycovid19$'daily recovered Cases', frequency Z 1,start Z c(15/02/2020,1)) plot(tsworldcovid19) A data driven predictive model approach for COVID-19 3 The 60-days COVID-19 forecasting graphs of register along recovery cases (Fig. 4), and normalized QQ plots 9 were computed ( Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…The arithmetic mean SD in each language condition and body sway axis was estimated for each participant, and the normality of the SD distribution for each language condition in the ML and AP axes was examined graphically via Q-Q plots (see Loy, Follett, & Hofmann, 2016) and statistically via the Shapiro-Wilk normality test (see Marmolejo-Ramos & González-Burgos, 2013). The Shapiro-Wilk test indicated that some vectors of data did not distribute normally in both AP and ML data; specifically, for the AP axis: W HE = 0.95, p = .2805, W LE = 0.93, p = .051, and W NE = 0.85, p < .001; and for the ML axis: W HE = 0.89, p = .004, W LE = 0.88, p = .003, and W NE = 0.87, p = .001.…”
Section: Methodsmentioning
confidence: 99%
“…In applications, we suggest using graphical checks via qq plots and plots of residuals against fitted values and covariates because such checks provide more information about the nature of the lack of fit than a p-value does. To get an understanding of the variability that would be expected in a qq plot if the model was correct it can also be useful to compare qq plots for the fitted model to a few qq plots for data generated from a standard normal distribution with the same sample size (Loy, Follett, & Hofmann, 2016).…”
Section: Scenario 1: Overdispersed Abundancementioning
confidence: 99%